Cross-resistance and synergy with bendamustine in chronic lymphocytic leukemia. (November 2016) - Kost, Sara E.F.; Bouchard, Eric D.J.; LaBossière, Élise; Ye, Xibiao; Queau, Michelle L.; Liang, William S.; Banerji, Versha; Gibson, Spencer B.; Katyal, Sachin; Johnston, James B.
Highlights: Cross-resistance is observed between BEN, CLB and FLU in CLL cells. Some BEN-resistant cells may respond to dADO/PEN. CLL cells with a del 17p display resistance to BEN, CLB and FLU. BEN induces apoptosis through the mitochondrial and death receptor pathways. Equivalent synergistic antitumor effect is observed between BEN and dADO/PEN or FLU. Abstract: Bendamustine (BEN) has structural similarities to an alkylating agent and a nucleoside analog, and effective against tumor cells that are resistant to standard therapy. In this study we compared the activities of BEN against that of the alkylating agent, chlorambucil (CLB), and the nucleoside analogs, fludarabine (FLU) and deoxyadenosine/pentostatin (dADO/PEN), in primary chronic lymphocytic leukemia (CLL) cells in vitro . Cross-resistance was observed between BEN, CLB and FLU, with previously treated patients or those with a deletion 17p being most resistant. In contrast, some resistant CLL cells retained moderate sensitivity to dADO/PEN. Like FLU and CLB, BEN induced apoptosis through both the mitochondrial and death receptor pathways. There was a greater increase in DNA double-strand breaks (DSB) following FLU, as compared to BEN and CLB. Synergistic cytotoxicity was seen on combining BEN or CLB with FLU or dADO/PEN, but not when combining BEN with CLB. These results demonstrate that BEN acts as an alkylating agent, demonstrates cross-resistance to CLB and FLU and resistance to cells with a del 17p. Synergistic cytotoxic activity was seen between BEN and dADO/PEN suggesting that the combination of BEN and PEN should be evaluated in the clinic.